Effect of Application, Duration and Dosing Frequency on the Efficacy and Adverse Effect of Adapalene in Acne Vulgaris: an Open-Label Randomized Controlled Study - Jha, Prasanna Kumar; Singh, Satyendra Kumar; Rai, Tulika (Nepalese Medical Journal, 2022)
Introduction: Topical retinoids are the mainstay of treatment for mild and moderate acne but longer duration of application causes adverse effects. The study aimed to evaluate the effect of application, duration, and dosing frequency on the efficacy and adverse effect of Adapalene in Acne Vulgaris. Materials and Methods: The study design was an open-label randomized controlled split-face trial. Patients with acne grades 1 and 2 were randomized into three groups using the split-face technique on the right and left sides. On the right side, patients applied adapalene daily in all the groups and alternately on the left face. The three groups of the study were overnight, 1 hour, and ½ hour application of adapalene. Follow up period was 4,8 and 12 weeks. Lesion count and side effects were evaluated at each follow-up. Results: Out of 292 who completed the study, the decrease in total lesion count was highest in the overnight group. Regarding specific lesion count, the decrease in non-inflammatory lesions was highest in the overnight group. However, short contact therapy with 1-hour application showed comparable efficacy with the overnight group in regards to inflammatory lesion count. There was a significant reduction of lesions in all groups from baseline to 12 weeks, with ½ hour group having minimal side effects followed by 1 hour and overnight. Conclusion: Short contact therapy for acne shows promising results in regard to efficacy and better tolerance.